RECENT STRONG EARTHQUAKES IN CENTRAL ASIA: REGULAR TECTONOPHYSICAL FEATURES OF LOCATIONS IN THE STRUCTURE AND GEODYNAMICS OF THE LITHOSPHERE. PART 1. MAIN GEODYNAMIC FACTORS PREDETERMINING LOCATIONS OF STRONG EARTHQUAKES IN THE STRUCTURE OF THE LITHOSPHER - S. I. Sherman; Ma Jin; E. A. Gorbunova (Геодинамика и тектонофизика, 2015)
Studying locations of strong earthquakes (М≥8) in space and time in Central Asia has been among top prob-lems for many years and still remains challenging for international research teams. The authors propose a new ap-proach that requires changing the paradigm of earthquake focus – solid rock relations, while this paradigm is a basis for practically all known physical models of earthquake foci. This paper describes the first step towards developing a new concept of the seismic process, including generation of strong earthquakes, with reference to specific geodynamic features of the part of the study region wherein strong earthquakes were recorded in the past two centuries. Our analysis of the locations of М≥8 earthquakes shows that in the past two centuries such earthquakes took place in areas of the dynamic influence of large deep faults in the western regions of Central Asia. In the continental Asia, there is a clear submeridional structural boundary (95–105°E) between the western and eastern regions, and this is a factor controlling localization of strong seismic events in the western regions. Obviously, the Indostan plate’s pressure from the south is an energy source for such events. The strong earthquakes are located in a relatively small part of the territory of Central Asia (i.e. the western regions), which is significantly different from its neighbouring areas at the north, east and west, as evidenced by its specific geodynamic parameters. (1) The crust is twice as thick in the western regions than in the eastern regions. (2) In the western regions, the block structures re-sulting from the crust destruction, which are mainly represented by lense-shaped forms elongated in the submeridio-nal direction, tend to dominate. (3) Active faults bordering large block structures are characterized by significant slip velocities that reach maximum values in the central part of the Tibetan plateau. Further northward, slip velocities decrease gradually, yet do not disappear. (4) In the western regions of Central Asia, the recurrence time of strong earthquakes is about 25 years. It correlates with the regular activation of the seismic process in Asia which is mani-fested in almost the same time intervals; a recurrence time of a strong earthquake controlled by a specific active fault exceeds seems 100–250 years. (5) Mechanisms of all the strong earthquakes contain a slip component that is often accompanied by a compression component. The slip component corresponds to shearing along the faults revealed by geological methods, i.e. correlates with rock mass displacements in the near-fault medium. (6) GPS geodetic meas-urements show that shearing develops in the NW direction in the Tibet. Further northward, the direction changes to the sublatitudinal one. At the boundary of ~105°E, southward of 30°N, the slip vectors attain the SE direction. Further southward of 20°N, at the eastern edge of the Himalayan thrust, the slip vectors again attain the sublatitudinal direc-tion. High velocities/rates of recent crust movements are typical of the Tibet region. (7) The NW direction is typical of the opposite vectors related to the Pacific subduction zone. The resultant of the NE and NW vectors provides for the right-lateral displacement of the rocks in the submeridional border zone. (8) The geodynamic zones around the cen-tral zone (wherein the strong earthquakes are located) are significantly less geodynamically active and thus facilitate the accumulation of compression stresses in the central zone, providing for the transition of rocks to the quazi-plastic state and even flow. This is the principal feature distinguishing the region, wherein the strong earthquakes are loca-ted, from its neighboring areas. In Central Asia, the structural positions of recent strong earthquakes are determined with respect to the following factors: (1) the western regions separated in the studied territory; (2) the larger thickness of the crust in the western regions; (3) strong submeridional compression of the crust and upper lithosphere in combination with shear stresses; (4) high rates of recent crustal movements; and (5) the rheological characteristics of the crust.